Tri Education Center Collaboration in Tackling Juvenile Delinquency in the Era of Globalization - Zaenuri, Zaenuri; Jenal, Ujang; Ali, Amum Mahbub; Yansyah, Dedy; Wahyudin, Mohamad (International Journal on Advanced Science, Education, and Religion, 2024)
Educational responsibility cannot be done unilaterally, it requires collaboration and cooperation of three components which Ki Hajar Dewantara called the three centers of education: family, educational institutions, and society. The three are a complete unit and complement each other. The involvement and role of parents and society in overseeing children's education in the era of globalization is very urgent.This journal aims to discuss the importance of the Three Centers of Education as a solution to overcome the increasing juvenile delinquency in this era of globalization. The writing of this journal uses the library research method, or often also called library study or library research, collecting data from various literatures. The three centers of education equally play an important role in the success of education, which are basically all interrelated and cooperate with each other. The three must indirectly provide close guidance in the education process. The relationship between the three can be seen from: Parents carry out their obligations to educate children in the family, educational institutions facilitate teaching various sciences. knowledge and skills with full support from parents of students, and the community is expected to become a facilitator for students to be able to actualize their knowledge and skills